Integrated Design Technology of Geological Engineering for Pressure Flooding and Water Injection in Low Permeability Reservoirs: Take the Reservoir of Keshang Formation in Wu2 East Area as an Example - Ming Qin; Chao Chen; Qingsen Yu; Zhenping Liu; Zhibo Liu; Hanlie Cheng; Fahim Theon (Journal of Chemistry)
The objective factors of low permeability reservoir determine that there is obvious starting pressure gradient in waterflooding development, and the injection pressure is high. Conventional waterflooding has the technical bottleneck of “no injection and no flooding.” It highlights the development contradictions such as serious under-injection, rapid production decline and difficult production of reserves. Pressurized water injection is a new technology of unconventional water injection to enhance oil recovery, which can improve the production degree of low permeability reservoir reserves and solve the problem of water injection difficulty. In order to ensure the reliability of scheme design and the success rate of field implementation, the key technologies of unconventional oil and gas reservoir geological engineering integration are applied for the first time, including 3D geological modeling technology, geomechanics modeling technology, complex fracture network simulation technology of geological engineering integration and numerical simulation technology, and a fine 3D dynamic and static model covering all elements of geology and engineering is objectively established. Through numerical simulation research, the optimal water injection parameters of pressure flooding are determined, and the implementation effect of the optimal scheme is predicted, which provides a scientific basis for field implementation.